Evidence Not Seen - Rose, Darlene Deibler; Nang ChanYeema (New York, USA HarperCollins Publishers, 2003)
The life of a Newlywed American missionary Darlene Deibler Rose survived 4 years in a notorious Japanese prison camp set deep in the jungles of New Guinea.
Keywords: Biography